Josef Steindl. Random processes and the growth of firms : a study of the Pareto Law. Londres : C. Griffin & Co., 1965. 249 p. - Garza H., Tomás (Estudios Demográficos y Urbanos, 1968)
JOSEF STEINDL, Randam Processes and the Growth of Firms: a Study of the Pareto Law. Londres, C. Griffin & Co., 1965.